Zonguldak Taşkömürünün Kuru Zenginleştirilmesi - Güldan, Günser (Fen Bilimleri Enstitüsü, 2011)
Kömür; çoğunlukla karbon, hidrojen ve oksijenden oluşan az miktarda kükürt ve azot içeren, kimyasal ve fiziksel olarak farklı yapıya sahip maden ve kayaçtır. Günümüzde elektrik üretimi, demir-çelik sanayi, çimento sektörü, ısınma ve diğer endüstri tesislerinde kullanılan kömür özellikle Türkiye’de klasik yaş yöntemlerle zenginleştirilmektedir. Ancak Amerika, Çin gibi ülkelerde kömür klasik yaş yöntemlere göre bir çok avantajı olan kuru zenginleştirme yöntemi ile de zenginleştirilebilmektedir. Kuru yöntemde kışın sert geçtiği bölgelerde, yaş yöntemde oluşan donma problemleri yaşanmaz ve su olmayan yörelerde tesis kurulmasına imkan yaratır. Aynı zamanda tesis binası ve işletme giderleri yaş yöntemlere göre daha azdır. Sonuç olarak, ülkemizde termik santralda yakılmak üzere üretilen kömürlerin değerlendirilmesi açısından kuru yöntemle zenginleştirme, termik santral verimini artırma açısından önemli bir alternatif olabilecektir. Kuru zenginleştirme ile yaş yöntemin kullanılması ile oluşan ek maliyetler azaltılabilecektir. Araştırma kapsamında uygulanan ilk yöntemde Zonguldak yöresinden getirilen taşkömürünün kuru zenginleştirmeye uygunluğu araştırılmıştır. İkinci yöntemde ise numune yaş olarak zenginleştirilerek iki yöntemin sonuçlarının karşılaştırılması yapılmıştır.

Coal is mine and a kind of rock which mostly contains of carbon, hydrogen and oxygen, contains small amount of sulphur and nitrogen, has different chemical and physical structure. Today, in Turkey, coal that is used in electricity generation, in iron-steel industry, in cement industry, in heating and other industrial plants, is richened with classical wet processing method. However in the USA and China, coal can be richened with dry processing method which has more advantages comparing to classical wet processing method. In dry processing, where the winter conditions are colder, does not have frost problems as in wet processing method and it also creates opportunity to build plants where there is no water available. Moreover, costs of merchant and expenses of plants are less compare to wet processing method. As a result, in respect to dry processing method is the assessment of coal which is to be used in thermoelectric power plant, will be an important advantage in increasing of effectiveness of thernoelectric power plant. With dry processing method, additional costs which results from wet processing method, will be reduced. In the first step which will be applied together with this research, a sample of mineral coal which was brought from Zonguldak area, will be analyzed whether it is suitable for dry processing method. In the second step, the sample will be richend with wet processing method. Then, the results of these two methods have been compared with each other.
An Hard Coal Investigation Into The Dry Cleaning Of Zonguldak
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2010
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2010
Keywords: Anahtar Kelimeler: Kuru Zenginleştirme; Taşkömürü; Yaş Zenginleştirme; Keywords: Coal; Dry Processing; Wet Processing